An Analysis of Focus on Form Practice in Communicative English Language Teaching Classrooms - Maizatulliza Muhamad; Richard Kiely (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
In communicative English language teaching classrooms, one of the main issues discussed is the teaching of forms. Research shows that Focus on Form (FoF) practice which focuses on building students’ communicative ability is effective and desirable in helping students acquire their second language. This is unlike Focus on Forms (FoFs) practice which emphasises building students grammatical accuracy. However, many of the studies on FoF practices are designed within a controlled environment with pre-determined categories, which is different from an actual classroom setting. This study is conducted in actual communicative English language teaching classrooms to investigate teachers’ FoF practices. Data were gathered from 15 non-participant classroom observations and interviews with three Malaysian ESL teachers. The data from the observations showed the teachers’ tendency to employ isolated form-focused instructions (I-FFI) and reactive FoF practices in teaching grammar. However, the interviews revealed that the teachers focused more on helping students to master grammatical rules which conformed to the principle of FoFs practice. The contradicting findings suggest a complexity of teachers’ actual practices which is not highlighted by many of the research studies in this area.